MANAGEMENT OVERVIEW: LEADERSHIP IN CHANGE - Johnson Kennedy, Posma Sariguna (Universitas Kristen Indonesia, 2020)
This paper aims to study how the leadership of an organization manages the process of change in its environment. The challenges faced are various changes both from within and outside the organization in a very fast, chaotic and turbulent, which has become the 'new' normal. The method of writing this paper is done through a study of various literatures. The COVID19 pandemic has various impacts on people's lives, especially business organizations or companies, which has caused many changes in the world of VUCA (Volatility, Uncertainty, Complexity and Ambiguity). Every organization must be able to identify it because every problem requires a fast and precise response. Each of these VUCA components presents challenges that need to be faced with Vision, Understanding, Clarity, and Agility. Keywords: Management, Leadership, Change, VUCA